2016
DOI: 10.3390/ijms17101619
|View full text |Cite
|
Sign up to set email alerts
|

Golgi-Related Proteins GOLPH2 (GP73/GOLM1) and GOLPH3 (GOPP1/MIDAS) in Cutaneous Melanoma: Patterns of Expression and Prognostic Significance

Abstract: GOLPH2 and GOLPH3 are Golgi-related proteins associated with aggressiveness and progression of a number of cancers. Their prognostic significance in melanoma has not yet been analyzed. We performed immunohistochemical analysis for GOLPH2 and GOLPH3 in 20 normal skin, 30 benign nevi and 100 primary melanoma tissue samples and evaluated their expression in three compartments: cancer cells, tumor-associated macrophages (TAMs) and cancer-associated fibroblasts (CAFs). High levels of both proteins in melanoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…GOLM1 is a resident cis-Golgi membrane protein. On the surface of the Golgi apparatus, there is an extensive C-terminal, coiled-coil domain and a single N-terminal transmembrane domain (44). It has been confirmed that the Golgi apparatus serves an active role in cell migration, which can be activated by post-translational modification and prominent alterations (45).…”
Section: Discussionmentioning
confidence: 93%
“…GOLM1 is a resident cis-Golgi membrane protein. On the surface of the Golgi apparatus, there is an extensive C-terminal, coiled-coil domain and a single N-terminal transmembrane domain (44). It has been confirmed that the Golgi apparatus serves an active role in cell migration, which can be activated by post-translational modification and prominent alterations (45).…”
Section: Discussionmentioning
confidence: 93%
“…These data point toward the potential use of Golgi trafficking genes as prognostic markers in cancer. To date, several Golgi-associated genes have been studied as prognostic markers in cancer, including Golgi phosphoprotein-3 (GOLPH3), Golgi protein 73 (GP73) and progestin and adipoQ receptor 3 (PAQR3) 57 60 . Further studies focused on elucidating the mechanisms regulating Golgi secretion capacity are warranted and may lead to therapeutic targeting of discrete components of this pathway in metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we observed a statistically significant correlation between the presence of macronucleoli and increased number of nucleoli (polynucleolization) and decreased expression of GOLPH3 protein in tumor-associated macrophages (TAMs). Having no factual insight into the role of GOLPH3 in TAMs, we only speculate that the reduced GOLPH3 immunoreactivity in TAMs may be associated with stable prooncogenic M2 phenotype [ 19 ]. Due to the lack of clinical and molecular data careful functional investigations are needed to explore the roles of tumor-associated macrophages in melanoma.…”
Section: Discussionmentioning
confidence: 99%